2012
DOI: 10.1039/c2dt00011c
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and cellular impact of dinuclear organoiridium DNA intercalators and nucleases with long rigid bridging ligands

Abstract: The DNA binding modes and cleavage properties of novel dinuclear Ir(III) polypyridyl (pp) complexes [{(η(5)-C(5)Me(5))Ir(pp)}(2)(μ-B)](CF(3)SO(3))(4) depend on the lengths of their rigid bridging dipyridinyl ligands B. Mono-intercalation and strong DNA cleavage properties were observed for the dipyrido[2,3-a:2',3'-c]phenazine (dppz) complexes 1 (B = 4-[(E)-2-(4-pyridinyl)ethenyl]pyridine) and 3 (B = 4-(2-pyridin-4-ylethynyl)pyridine), whose intracationic Ir···Ir' distances are about 13.1 and 13.3 Å, respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 55 publications
(67 reference statements)
1
24
0
Order By: Relevance
“…Whereas RhCp* complexes formed with 2-picolinic acid (pic) [12] and 3-hydroxy(thio)pyrones derivatized by morpholine, piperidine or N-methylpyrazine moieties [13] exhibited only poor or no bioactivity. Promising in vitro antiproliferative activities have been reported for the RhCp* complexes of (N,N) polypyridyl (pp) ligands by Sheldrick et al [14][15][16][17] possessing IC 50 values in the low micromolar range. However, the RhCp* complexes of the simplest bidentate alkylamino and aromatic N-donor ligands, namely ethylenediamine (en) and 2,2'-bipyridine (bpy) did not show significant cytotoxicity (IC 50 >100 μM measured in MCF-7 and HT-29 cells) [17].…”
Section: Compounds Namely Imidazolium Trans-[tetrachlorido(dmso)(imimentioning
confidence: 99%
“…Whereas RhCp* complexes formed with 2-picolinic acid (pic) [12] and 3-hydroxy(thio)pyrones derivatized by morpholine, piperidine or N-methylpyrazine moieties [13] exhibited only poor or no bioactivity. Promising in vitro antiproliferative activities have been reported for the RhCp* complexes of (N,N) polypyridyl (pp) ligands by Sheldrick et al [14][15][16][17] possessing IC 50 values in the low micromolar range. However, the RhCp* complexes of the simplest bidentate alkylamino and aromatic N-donor ligands, namely ethylenediamine (en) and 2,2'-bipyridine (bpy) did not show significant cytotoxicity (IC 50 >100 μM measured in MCF-7 and HT-29 cells) [17].…”
Section: Compounds Namely Imidazolium Trans-[tetrachlorido(dmso)(imimentioning
confidence: 99%
“…[15] Polypyridyl-containing iridium half-sandwich complexes have been demonstrated by the groups of Sadler and Sheldrick to bind to DNA through intercalative and/or covalent binding modes. [16] In contrast, Sheldrick and co-workers have found that a number of other polypyridyl-containing trichloro iridium and rhodium complexes surprisingly did not significantly interact with DNA. [17] To explore this issue further, we investigated the ability of the complexes 10-35, identified from the second round of screening, to interact with DNA by using fluorescence resonance energy transfer (FRET) melting experiments ( Figure S5 shows representative spectra for 12).…”
mentioning
confidence: 91%
“…16 Therefore, breaking up the rhodium and iridium dihalide Cp* dimers with different bidentate ligands led to the development of complexes which show high in vitro cytotoxic activity against tumour cell lines. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Where tested, studies have reported negligible activities of the starting dimers, i.e. [Cp*MCl 2 ] 2 (M = Rh or Ir) 16 (M = Rh or Ir).…”
mentioning
confidence: 99%